2023
DOI: 10.3390/v15020410
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cucurbit Aphid-Borne Yellows Virus (CABYV) from Passion Fruit in Brazil: Evidence of a Complex of Species within CABYV Isolates

Abstract: High-throughput sequencing (HTS) has been an important tool for the discovery of plant viruses and their surveillance. In 2015, several virus-like symptoms were observed in passion fruit (PF) plants in Bahia state, Brazil. Using HTS technology, bioinformatics tools, RT-PCR, and Sanger sequencing, we identified the cucurbit aphid-borne yellows virus (CABYV, Polerovirus, Solemoviridae) in co-infection with cowpea aphid-borne mosaic virus (CABMV, Potyvirus, Potyviridae) in PF, in green manure, and spontaneous pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The analysis showed that the CABYV isolates formed two distinct phylogenetic clusters, with one cluster containing isolates from Africa and Asia, while the other cluster comprising isolates from Europe. Additionally, several recombination events were identified within the CABYV genome, which may have contributed to the emergence and diversification of new strains of the virus [ 14 ]. High-throughput sequencing was used to analyze the genetic diversity of CABYV isolates collected from Spain and other European countries.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis showed that the CABYV isolates formed two distinct phylogenetic clusters, with one cluster containing isolates from Africa and Asia, while the other cluster comprising isolates from Europe. Additionally, several recombination events were identified within the CABYV genome, which may have contributed to the emergence and diversification of new strains of the virus [ 14 ]. High-throughput sequencing was used to analyze the genetic diversity of CABYV isolates collected from Spain and other European countries.…”
Section: Introductionmentioning
confidence: 99%